Variation in the chemical composition of essential oils from Mangifera indica L. leaves by comprehensive two-dimensional gas chromatography - Cardoso, Claudia Andrea Lima; Caramão, Elina Bastos; Castro, Thiago Luis Aguayo de; Simionatto, Euclesio (Eclética Química, 2023)
The leaves of Mangifera indica L. have been used in the medical system of India to treat diseases such as asthma, dysentery, cough, leucorrhea, jaundice, pain, and malaria. The analysis of different varieties of the same species is intended to determine if the compounds have a differential distribution. The present study investigates the volatile compounds from the leaves of two M. indica varieties extracted by hydrodistillation and analyzed by comprehensive two-dimensional gas chromatography coupled to time-of-flight mass spectrometry (GC×GC/TOFMS). The number of compounds identified by GC×GC/TOFMS was superior to that obtained by gas chromatography/mass spectrometry (GC/MS) for the same variety of M. indica. This study demonstrates the applicability of the GC×GC/TOFMS for the comprehensive profiling of essential oils from M. indica, in which 125 and 95 compounds were identified in the varieties ‘espada’ and ‘coração de boi’, respectively. These results show that the compositions of the two analyzed essential oils present differences concerning the GC×GC/TOFMS and conventional chromatography technique, the GC/MS.